Education for Project Leaders (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
At present, education within the field of Project Management in Slovak and the Czech Republic is carried out via commercial entities or within higher education, and the most used contents are the commonly used methodologies of project management. From the methodology perspective, the most critical areas are preparation of the project plan, resource planning and project realization following the methodology. However, completing a methodology training certificate or obtaining a university degree diploma does not automatically mean the success of the project or the success of the project leader. People are the critical element on which the project's success depends – whether they are the stakeholders, the end users, external or internal team members. This paper focuses on the real experiences of working project managers on their knowledge, skills, and talents regarding leadership and human skills. At the same time, it explores the elements that they consider key to the success of the projects they have led and successfully delivered. The result of this research is one of the inputs for creating a model for a comprehensive education of project leaders in leadership and human skills.